Hubungan Dukungan Suami dan Pengetahuan Terhadap Penggunaan Alat Kontrasepsi - Ramayani Ramayani; Nency Agustia (JURNAL BIDANG ILMU KESEHATAN, 2025)
The Family Planning Program is an integrated part of the national development program, aiming to achieve balanced population growth in Indonesia, thereby achieving economic, spiritual, and socio-cultural well-being. The objective of this study was to determine the relationship between husband's support and knowledge regarding contraceptive use at the TPMB Ririn Sevda Korini, SKM., S.Keb, Ogan Komering Ulu Regency. This study employed a quantitative correlation method with a cross-sectional approach. The variables studied were presented in the form of a frequency distribution table and tested using univariate analysis using a demographic data questionnaire. Bivariate analysis used chi-square analysis. The sample size was 100 respondents. The chi-square test yielded a ρ value of 0.000, indicating a relationship between husband's support and contraceptive use at the TPMB Ririn Sevda Korini, SKM., S.Keb, Ogan Komering Ulu Regency. The chi-square test results obtained a ρ value of 0.000, indicating a relationship between knowledge and contraceptive use at TPMB Ririn Sevda Korini, SKM., S.Keb, Ogan Komering Ulu Regency. The conclusion of this study is that husbands' support can influence wives' contraceptive use because wives do not experience the negative effects of severe stress on their reproductive health. Respondents' high levels of knowledge can reflect broader perspectives, facilitating the acceptance of new innovations and making appropriate decisions